Allostatic load in patients with breast cancer - K. F. Makkonen; N. M. Agarkov; U. S. Stanoevich; A. A. Titov; M. S. Mitikhina; E. A. Moskaleva (Сибирский онкологический журнал)
Breast cancer is the most common cancer in women worldwide. However, the allostatic load in breast cancer patients has not been sufficiently studied. Objective: to study the allostatic load in middle-aged and elderly patients with breast cancer. Material and methods. The study included 65 middle-aged and 60 elderly patients with histologically confirmed breast cancer and 45 people aged 60-74 years, who had no breast cancer. The allostatic load was studied in these three groups according to the level: systolic and diastolic blood pressure, total cholesterol, triglycerides, high and low density lipoproteins, glucose, albumins and waist circumference. Results. The allostatic load score was significantly higher in elderly breast cancer patients than in middle-aged breast cancer patients (4.3 ± 0.3 points versus 2.9 ± 0.2 points, p<0.01). In addition, the allostatic load score in the middle-aged patients with breast cancer was significantly higher (2.7 ± 0.2 points) than in people of the same age, who had no breast cancer (1.6 ± 0.1 points). In elderly patients, the allostatic load score was also significantly higher in patients with breast cancer than in people without breast cancer (4.3 ± 0.3 points and 2.9 ± 0.2 points, respectively; p<0.001). Significant differences in the allostatic load parameters, such as the levels of total cholesterol (5.8 ± 1.3 mmol/l versus 4.0 ± 0.8 mmol/l), and albumin (45.1 ± 7.4 % versus 61.4 ± 7.6 %) were found between breast cancer patients aged 60-74 years and people of an identical age, who had no breast cancer. statistically significant differences in allostatic load biomarkers, such as systolic blood pressure, diastolic blood pressure, blood levels of triglycerides and glucose, and waist circumference were found between elderly patients with breast cancer and age controls (without breast cancer). The content of triglycerides in the blood of patients aged 60-74 years with breast cancer was 1.8 times higher than that in patients of the same age with no breast cancer (p<0.001). The blood glucose level was significantly higher in patients with breast cancer than in the age controls (5.8 ± 1.2 g/l versus 4.4 ± 1.1 g/l, p<0.01). Conclusion. The allostatic load and its variables should be used as biomarkers of increased risk of breast cancer.